Blockchain solutions for generative AI challenges in journalism - Picha Edwardsson, Malin; Al-Saqaf, Walid (Frontiers in Blockchain, 2024)
This study aims to identify and assess AI and blockchain solutions in relation to journalistic authenticity and integrity. Central to our exploration is the role of blockchain technology in verifying content provenance. As a key component of a global Web3 framework, blockchain could offer a foundation for authenticating the origins of content. In this article, we explore how blockchain, with its capacity for creating immutable and cryptographically signed data records, could be applied by journalists to verify photos, videos and documents. Our analysis identified nine blockchain-based solutions for content verification, with three platforms -Attestiv, OriginStamp, and Fact Protocolshowing particular promise for journalistic workflows. We conclude that while AI and blockchain solutions are currently available to journalists today, they require high-level technical expertise. Many media companies are now venturing into this field as well, thus affecting the professional role of journalists in general. In our study, it is evident that integrating AI and blockchain in journalism is not merely about adopting new tools but also about understanding their broader implications for journalism as a profession and the convergence in society. The focus must remain on enhancing journalistic integrity and public trust to ensure that these technological advances benefit the field of journalism and, by extension, the democratic processes it supports.